Pengaruh Literasi Keuangan, Locus of Control, dan Financial Self Efficacy Terhadap Perilaku Manajemen Keuangan - Atik Atikah; Rocky Rinaldi Kurniawan (JMB : Jurnal Manajemen dan Bisnis, 2021)
Financial management is an important thing for everyone to learn. The ability to manage finances can determine how each individual lives in the future. Good financial management can help raise the level of welfare of the People of Indonesia. This study aims to examine the influence of financial literacy, locus of control, and financial self-efficacy on financial management behavior in PT employees. Panarub Industry. This research is associative research with a quantitative approach. The population in this study was employees who worked at PT. Panarub Industry in the auto cutting department. The samples studied numbered 80 people. The analysis method used is test F and t using SPSS version 25. The results showed that there is an influence between financial literacy, locus of control, and financial self-efficacy on the behavior of financial management partially and simultaneously.